Aneuploidy in the transgenic rabbit - Parkányi, V; Chrenek, P; Rafay, J; Süvegová, K; Jurcík, R; Makarevich, A V; Pivko, J; Hetényi, L; Paleyanda, R K (Folia biologica, 2004)
The aim of this study was to determine whether there are differences in the karyotypes between transgenic and non-transgenic or control rabbits. New Zealand White transgenic rabbits (F1 generation) were obtained after breeding of transgenic founder rabbits that were derived from single--SM--or double microinjection--DM--with a WAP-hFVIII transgene. C-metaphase plates were obtained from short-time culture of peripheral blood lymphocytes synchronized by the addition of colcemide. A significantly higher rate of aneuploidy was observed in c-metaphase spreads of transgenic (56-66%) rabbits, as compared to non-transgenic ones (28-38%) (P < 0.05; P < 0.01). The patterns of chromosome banding were identical in both groups of rabbits. No structural aberrations were revealed in either group. These findings demonstrate that transgenic rabbits have a higher frequency of numerical chromosomal aberrations in their peripheral blood lymphocytes than normal rabbits, but without apparent deleterious effects on health or reproduction.
Keywords: Animals; králíci; aneuploidie; Animals, Genetically Modified; ženské pohlaví; mužské pohlaví; Metaphase; Chromosomes; Aneuploidy; Diploidy; Breeding; metafáze; Karyotyping; Male; lymfocyty; chov; zvířata; Lymphocytes; Chromosome Banding; geneticky modifikovaná zvířata; Rabbits; pruhování chromozomů; chromozomy; diploidie; karyotypizace; Female